2013
DOI: 10.1097/mat.0b013e3182816a75
|View full text |Cite
|
Sign up to set email alerts
|

Newly Designed CRRT Membranes for Sepsis and SIRS—A Pragmatic Approach for Bedside Intensivists Summarizing the More Recent Advances

Abstract: In recent years, after all the attention has been focused on the dose for continuous renal replacement therapy (CRRT) in sepsis and systemic inflammation response syndrome (SIRS), the relatively negative results of all those studies did urge our expectations on new approaches regarding CRRT in sepsis and SIRS. So far, after the failure of the major randomized studies on dose, attention is now drawn to new membranes that could better eliminate massive amounts of unbound mediators in wider spectrum and also in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 50 publications
4
104
0
7
Order By: Relevance
“…Early saturation is unlikely and frequent membrane changes (e.g. every 12-24 h) are not necessary [17,19]. This is corroborated by our experience in a small cohort of patients who supported colistin doses as high as 4.5 million IU t.i.d.…”
Section: Crrt-related Strategies To Avoid Colistin Toxicitysupporting
confidence: 69%
See 2 more Smart Citations
“…Early saturation is unlikely and frequent membrane changes (e.g. every 12-24 h) are not necessary [17,19]. This is corroborated by our experience in a small cohort of patients who supported colistin doses as high as 4.5 million IU t.i.d.…”
Section: Crrt-related Strategies To Avoid Colistin Toxicitysupporting
confidence: 69%
“…In contrast, the novel AN69 ST (acrylonitrile 69 surface treated) membrane allows much higher clearance through adsorption. Elimination occurs in part at the (rapidly saturated) membrane surface but predominantly in its (less easily saturated) bulk [19]. Early saturation is unlikely and frequent membrane changes (e.g.…”
Section: Crrt-related Strategies To Avoid Colistin Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Switzerland, an RCT that compares the efficacy of oXiris®-CVVH and PMX-DHP in patients with septic shock is currently in progress (ENDoX study). Furthermore, Honore et al state in their review article that they are planning an RCT to compare four different membrane hemofilters (AN69, AN69ST, oXiris®, and PAES) in septic shock with AKI [48].…”
Section: Modified An69st (Oxiris®)mentioning
confidence: 99%
“…Nosaka et al recently showed that administration of a monoclonal antibody against HMGB-1 suppressed the immuno-inflammatory response and significantly improved severe lung injury and survival in patients affected with H1N1 influenza A virus [15]. HMGB-1 is also effectively cleared by highly adsorptive dialysis membranes such as the acrylonitrile 69 surface-treated filter [16] which is increasingly used for continuous renal replacement therapy (CRRT) in hemodynamically unstable septic patients [17]. Though obviously an attractive and more easily available alternative for counteracting the noxious effects of HMGB-1, clinical efficacy and benefit of such CRRT approach has not yet been established.…”
mentioning
confidence: 99%